Aging Microglia—Phenotypes, Functions and Implications for Age-Related Neurodegenerative Diseases - Spittau, Björn (Frontiers in Aging Neuroscience, 2017)
Aging of the central nervous system is one of the major risk factors for the development of neurodegenerative pathologies such as Parkinson´s disease (PD) and Alzheimer´s disease (AD). The molecular mechanisms underlying the onset of AD and especially PD are not well understood. However, neuroinflammatory responses mediated by microglia as the resident immune cells of the central nervous system (CNS) have been reported for both diseases. The unique nature and developmental origin of microglia causing microglial self-renewal and telomere shortening led to the hypothesis that these CNS-specific innate immune cells become senescent. Age-dependent and senescence-driven impairments of microglia functions and responses have been suggested to play essential roles during onset and progression of neurodegenerative diseases. This review summarizes the current knowledge of microglia phenotypes and functions in the aging CNS and further discusses the implications of these age-dependent microglia changes for the development and progression of AD and PD as the most common neurodegenerative diseases.